DOES ENTREPRENEURIAL SPIRIT MATTER FOR JOB CREATION IN KADUNA STATE? (Journal of the Management Sciences, 2025)
Job creation has been widely acknowledged as ways of achieving economic development through generation of entrepreneurial mindset which is capable of reducing social vices. This study adopted a descriptive survey approach and 489 respondents were sampled using proportionate stratified sampling technique from the population of 15558 small businesses across the twenty three Local Government Areas in Kaduna State Nigeria. The findings indicated a positive relationship between entrepreneurial spirit and job creation. The study recommended that policy makers should provides appropriate entrepreneurial ecosystem that will foster the development of entrepreneurial spirit as it is capable of improving job creation which fosters economic development.
Keywords: Entrepreneurial Spirit; Job Creation; Resourcefulness; Risk taking; Self-efficacy